CHARACTERISATION PROCEDURES IN THE NOVEL POSLIJE ZABAVE BY STEVO GRABOVAC - Jelena G. Reljić (Filolog, 2025)
The novel After Party (Poslije zabave) by Stevo Grabovac is very complex in structural and thematic terms. This paper, through a narratological approach to the novel, analyses characterisation procedures. In this respect, the dominant procedure is indirect characterisation through the actions of characters and through their interactions with other characters. The characters are complex and they undergo the process of transformation. Taking into account the issue of classification of characters and the impossibility of placing them within a single general theory, the paper highlights only the most prominent procedures as regards the novel and leaves room for more comprehensive analyses.